2013
DOI: 10.3109/15563650.2013.839028
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing risk factors for pediatric lamp oil product exposures

Abstract: Poisonings from lamp oil ingestion continue to occur worldwide among the pediatric population despite preventive measures such as restricted sale of colored and scented lamp oils. This suggests that optimal prevention practices for unintentional pediatric exposures to lamp oil have yet to be identified and/or properly implemented. Objective To characterize demographic, health data, and potential risk factors associated with reported exposures to lamp oil by callers to poison centers (PCs) in the US and discu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 8 publications
2
24
0
Order By: Relevance
“…The highest rates of morbidity and mortality result from accidental ingestion by children younger than 5 years in US (Makrygianni et al, 2016). Sheikh et al (2013), found that upon ingestion in US, 35-54% of children are symptomatic. This is because hydrocarbon aspiration may cause death secondary to respiratory failure in this pediatric population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest rates of morbidity and mortality result from accidental ingestion by children younger than 5 years in US (Makrygianni et al, 2016). Sheikh et al (2013), found that upon ingestion in US, 35-54% of children are symptomatic. This is because hydrocarbon aspiration may cause death secondary to respiratory failure in this pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Among hydrocarbons those with low viscosity and surface tension, such as kerosene, lighter fluid, lamp oil, and naphtha, are frequently associated with clinically significant effects on the respiratory system. Chemical pneumonitis, respiratory distress, and a variety of air-leak syndromes may occur (Sheikh et al, 2013). In a study made by Makrygianni et al (2016) in US, aspiration pneumonitis occurred in approximately 15% of ingestions, and evolves over the first 6-8 hours Chest radiographic abnormalities develop by 4-8 hours after ingestion, but they are not always predictive of clinical pneumonitis.…”
Section: Discussionmentioning
confidence: 99%
“…It is found that, in general, accidents are less frequent among children under one. In the context of the AH caused by a specific cause, the poisonings or intoxications were also analyzed from the age of the child in seven surveys (18,21,(26)(27)30,32,41) . The same analysis was performed in cases of accidental drowning/submersion injuries in childhood (33) and television falling on the child (37) .…”
Section: Category 1 -Proximal Social Determinants Of Healthmentioning
confidence: 99%
“…Behavioral factors, especially those related to the lack of adult supervision, were identified in a large part of the articles analyz ed (18,23,(25)(26)(28)(29)(30)(31)(32)(33)(36)(37)39,41,43,48) . The main AHs that were related to this determinant were: intoxications; falls and burns (18,21,26,30,32,41,48) . In such contexts, direct adult supervision is one of the protective factors to prevent childhood accidents.…”
Section: Category 2 -Intermediate Social Determinants Of Healthmentioning
confidence: 99%
See 1 more Smart Citation